A virtue theoretic ethics of intellectual agency - RYAN, Shane (Institutional Knowledge at Singapore Management University, 2022)
There is a well-established literature on the ethics of belief. Our beliefs, however, are just one aspect of our intellectual lives with which epistemology should be concerned. I make the case that epistemologists should be concerned with an ethics of intellectual agency rather than the narrower category of ethics of belief. Various species of normativity, epistemic, moral, and so on, that may be relevant to the ethics of belief are laid out. An account adapted from virtue ethics for an ethics that goes beyond the ethics of belief is defended. The main claim advanced here is that we should act as the virtuous agent would characteristically act in the circumstances. This claim is supported with reference to a number of examples, as well as considerations informing virtue ethics. An acknowledged feature of this account is that it provides limited guidance regarding right action in intellectual agency. While the account draws on virtue responsibilism to offer guidance, the case is made that it’s a mistake to think that an account in this area can provide a successful decision procedure.